Analysis of Factors Affecting Work Performance Assessment Through Employee Work Targets at the Jayapura City Personnel, Education and Training Agency - Sapioper, Hiskia C. M.; Yumame, Jackson (CV. Proaksara Global Transeduka, 2025)
The primary objective of this research is to examine the various factors that impact the evaluation of job performance based on set targets for employees at the Jayapura City Personnel, Education and Training Agency. The research methodology employed for this study involves a qualitative approach. The sources of data for the study were gathered from observations, interviews, documentation, and review of existing literature. The data analysis process consists of several stages including data presentation, data reduction, drawing conclusions, and verification. The findings of this study suggest that evaluating job performance through employee work targets aligns well with the criteria for job performance assessment. This approach allows for the measurement of job quality, productivity, teamwork, punctuality, and expertise in the role. As for internal constraints, it consists of two factors, namely from employees or staff who are considered not disciplined and obedient to existing rules and there are other work units that feel that work support facilities such as computers and network disruptions are needed to support smooth work. As a recommendation, employee performance appraisal within the Jayapura City Personnel, Education and Training Agency should be further improved and carried out properly.